New PKS-NRPS tetramic acids and pyridinone from an Australian marine-derived fungus, Chaunopycnis sp.1. Issue 28 (28th July 2015) - Shang, Zhuo; Li, Li; Espósito, Breno P.; Salim, Angela A.; Khalil, Zeinab G.; Quezada, Michelle; Bernhardt, Paul V.; Capon, Robert J.
<x xml:space="preserve">Abstract</x> Marine-derived fungus Chaunopycnis sp. yielded the tetramic acid F-14329 (1) and new analogues, chaunolidines A–C (2–4), together with the new pyridinone chaunolidone A (5), and pyridoxatin (6).